Social and Professional Portrait of University Teachers (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Relevance. The strategy for the development of science and technology of the Republic of Uzbekistan for the period until 2021 provides for a special program for the development of medical science, one of the objectives of which is “the development of technology for assessing the processes of adaptation and the formation of pathological disorders under acute and chronic influence of physical, chemical, biological factors of the production environment and labor process, as well as disease prevention, taking into account individual sensitivity (depending on the typological characteristics of the central nervous system, genetic and other indicators).” This task involves conducting a wide range of studies relating to various aspects of the health of the widest possible range of populations, taking into account the specific conditions of its life and changing living conditions.